PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PABRIK KRUPUK JOGYA SARI UDANG KLEDUNG KRADENAN BANYUURIP PURWOREJO - Sundari, Retno (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2023)
Human resources have a very important position in an organization’s goals. Company goals are not dependent on modern tools but the success of an organization is strongly influenced by individual performance performed by employees. Several ways to achieve good performance can be achieved by empowering employees such as aducation, training, and compensation. This study aimed to determine the effect of compensation on employee performance at factory Krupuk Jogya Sari Udang Kledung Kradenan Banyuurip Purworejo. Subjects in this research are employees who work on Pabrik Krupuk Jogya Sari Udsng Kledung Kradenan Banyuurip Purworejo factory for 40 people. Research method using quantitative method whole collection techniques used in this research is a questionnaire that had been tested and have met the requirements for validity and reliability, while data analysis using multiple regression analysis. Results of t-test analysis note that the value of the variable significance of compensation amouting to 0,038 less than the requisite criteria for testing the 0.05 (5%). This means compensation significantly affect the performance employees at Pabrik Krupuk Jogya Sari Udang Kledung Kradenan Banyuurip Purworejo.